Differential effects of public and private funding in the medical device industry. (1st February 2018) - Kang, Hyunsung D.; Ku, David N.
ABSTRACT: Introduction : Funding for scientific advancement comes from two dominant sources: public funds used to generate knowledge, and private sector funds in the pursuit of commercial products. It is unclear how to compare the outputs of these two financial mechanisms because both sectors are motivated by common goods but are also governed by divergent forces. Employment within a geographic region may be a metric of mutual value that can be applied equally to assess the societal impacts of two financing sources. Areas covered : The authors focused on the medical device industry, which is a robust sector of growth for the U.S. economy. The U.S. NIH and venture capital community are representatives of public and private capital, respectively. Using a longitudinal employment dataset of 247 distinct locations, the authors found that NIH funding tends to create more jobs directly compared to venture capital funding. Moreover, the indirect effect of governmental funding is initially smaller than that of venture capital funding for the first two years, but eventually surpasses that of venture capital funding. Expert commentary : These findings imply that policy decisions regarding financial allocations in the medical device industry should consider the appropriate typology of financial capital and its consequences.